Morphological characterization of seedlings of five tree species from the tropical semideciduous forest, Brazil - Lopes, Aline; Rosa-Osman, Sônia Maciel da; Piedade, Maria Teresa Fernandez (Floresta, 2012)
The tree species Astronium graveolens (Anacardiaceae), Cedrela fissilis (Meliaceae), Gallesia integrifolia (Phytolaccaceae), Parapiptadenia rigida (Fabaceae) and Tabebuia avellanedae (Bignoniaceae) are found in remnants of tropical semideciduous forest in the North and Northwest of Paraná State and interior of the State of São Paulo. This study describes the morphological characteristics of seedlings in order to enable their identification in the field. Seedlings analyzed proved to be morphologically distinct from their cotyledons to eophylls and metaphylls and they may easily be distinguished in the plant community. All species showed leaves with petioles, and only C. fissilis and T. avellanedae presented eophylls. Cedrela fissilis has compounded eophyll, trifoliate, with integral edge, while in T. avellanedae it is simple, with serrated edge. Seedlings of G. integrifolia presented simple mesophyll, while the metaphyslls of C. fissilis, T. avellanedae and A. graveolens metaphylls are compounded; in P. rigida the metaphyll is bipinate. Since seedlings were visually distinct, the field's identification is possible.
Caracterização morfológica das plântulas de cinco espécies arbóreas da floresta estacional semidecidual, Brasil
Keywords: Anacardiaceae; Astronium Graveolens; Bignoniaceae; Cedrela; Cedrela Fissilis; Fabaceae; Gallesia Integrifolia; Meliaceae; Parapiptadenia Rigida; Phytolaccaceae; Tabebuia; Tabebuia Avellanedae